Electrophysiological analysis of mammalian cells expressing hERG using automated 384-well-patch-clamp. Issue 1 (December 2015) - Haraguchi, Yuji; Ohtsuki, Atsushi; Oka, Takayuki; Shimizu, Tatsuya
Abstract Background An in vitro electrophysiological assay system, which can assess compound effects and thus show cardiotoxicity including arrhythmia risks of test drugs, is an essential method in the field of drug development and toxicology. Methods In this study, high-throughput electrophysiological recordings of human embryonic kidney (HEK 293) cells and Chinese hamster ovary (CHO) cells stably expressing human ether-a-go-go related gene (hERG) were performed utilizing an automated 384-well-patch-clamp system, which records up to 384 cells simultaneously. hERG channel inhibition, which is closely related to a drug-induced QT prolongation and is increasing the risk of sudden cardiac death, was investigated in the high-throughput screening patch-clamp system. Results In the automated patch-clamp measurements performed here, Kv currents were investigated with high efficiency. Various hERG channel blockers showed concentration-dependent inhibition, the 50 % inhibitory concentrations (IC50 ) of those blockers were in good agreement with previous reports. Conclusions The high-throughput patch-clamp system has a high potential in the field of pharmacology, toxicology, and cardiac physiology, and will contribute to the acceleration of pharmaceutical drug development and drug safety testing.